(3TQM ebOeI cTa GdZWGAs - (3GdfLaj, MSf Hf LYaQ GdfLaj, J (B1262(3g` (B1846(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdebUO GdChd, heG jJYdb HHjGf HYV GdeWGdH GdCUhdjI GdaQYjI hajg CHMGK Tehd GdebUO ddEHMGK hJShjJgGs
(3BNQgG (B:s
(3BNQgG(B: (3hgPG cdg dJfHjg GdZGadjf Yf GdCUhd GdcdjI (B.. (3GdabgjI aj GdeSGFd GdLRFjI hGdebGeGJ GdabgjI JQGLjM dG JMUi hGfXGQ dG JSJbUi jYQagG ef ehGQO Gdabgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 186s
(3GdPQjYI, L (B13: 62s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs